(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
The social experience formed in the educational environment can either promote or hinder a high school student’s successful integration into society. In this context, bullying, as intense and systematic psychological or physical pressure, becomes a serious challenge for both the student and the educational system. It is not new to our reality; it has simply taken on a new quality and resonance. The manifestations and motivations are varied, but the consequences are the same: the process of personality formation and socialization of the high school student who is subjected to bullying is distorted. Moreover, bullying disrupts the high school student’s social interactions, leading to self-abasement or, conversely, the reinforcement of aggressive behavior. Nevertheless, bullying is still viewed not as a challenge, but as an age-related characteristic and an inability to manage emotions. To study and analyze the possible forms of bullying manifestation in high school that hinder the high school student’s socialization and identity formation.